Association between time from diagnosis to initiation of systemic therapy of metastatic renal cell carcinoma with treatment outcome - Lisičić, Nikola; Kević, Angelina; Savić, Marko; Nikić, Predrag (Medicinski podmladak, 2023)
Introduction: In about 30% of cases, renal cell carcinoma (RCC) is detected initialy in the metastatic stage (mRCC). The mainstay of mRCC treatment is anti-angiogenesis targeted therapy and immunotherapy that both have significantly prolonged progression-free survival and overall survival in patients with mRCC.Aim: The aim of this study was to examine the association between time interval from diagnosis of mRCC to the start of systemic therapy with the radiologically assessed best treatment response after 12 months of therapy.Material and methods: This observational study included 85 patients diagnosed initially in the metastatic stage of RCC. All patients received single agent systemic targeted therapy sunitinib. The minimum follow-up period was 12 months. Radiologic assessment was performed after every 3 months, and the RECIST criteria were used to evaluate the best treatment response.Ressults: The mean time interval from mRCC diagnosis to the start of systemic targeted therapy was 3.5 ± 2.5 months, with a median of 2 months. No statistically significant association was observed between the best radiologically assessed treatment response after 12 months of therapy and time interval  from diagnosis of mRCC to the start of systemic targeted therapy (p = 0.7). Moreover, no statistically significant association was found between the best radiologically assessed treatment response after 12 months of therapy and total number of metastatic sites at baseline.Conclusion:  No association was observed between the best radiologically assessed treatment response after 12 months of systemic targeted therapy, neither with time interval from mRCC diagnosis to the start of systemic targeted therapy, nor with the total number of metastatic sites in patients who were initially diagnosed with mRCC and received sunitinib in first line setting.
Keywords: Keywords: mRCC, systemic therapy, treatment response, observational study, sunitinib